O brincar de crianças em idade pré-escolar com deficiência Intelectual: considerações teóricas a partir de Vigotski - Grabowski, Bruna Silva (My University, 2025)
This dissertation focuses on the study of the development and learning of children with intellectual disabilities. The theoretical perspective chosen is the historical-cultural theory and the social model of disability. It is also understood that playing is essential for child development, as it promotes development and learning through the expansion of higher psychic functions, strengthening of affective bonds and access to cultural assets. In this sense, connections between disability and play are woven. Thus, the general objective of the research is to investigate the play of children with intellectual disabilities at preschool age (from 3 to 6 years old), in light of the historical-cultural theory. The specific objectives are: a) to characterize intellectual disability based on the assumptions of Vygotsky's historicalcultural theory and the perspective of the social model of disability; b) to explain concepts of Vygotsky's historical-cultural theory, which are central to understanding the development and learning of children with intellectual disabilities; c) to describe play in early childhood education, focusing on the contributions of classical and contemporary historical-cultural theory; d) to establish, based on historical-cultural theory, the axes for thinking about the play of children with intellectual disabilities at preschool age, in order to indicate possible interventions for the fields of education and psychology. This is a qualitative, exploratory study, whose methodological path consists of theoretical-conceptual research. The analytical mode of knowledge was chosen as the production of scientific knowledge. The results of the research demonstrate that "make-belive play" is the guiding activity of preschool children, being fundamental for the development of imagination and creativity, emancipation from reality, recognition of social roles, zone of proximal development and higher psychological functions also for children with intellectual disabilities. Furthermore, collective play of children with intellectual disabilities with their peers (with or without disabilities) and adults favors social interaction, playfulness, imagination, imitation, development of higher psychological functions, especially thought, speech, memory and attention, and the creation of the zone of proximal development, thanks to the mediation of the teacher. It is concluded that, for preschool-aged children with intellectual disabilities, both "make-belive play" and collective play are ways of accessing cultural and social assets and, therefore, of expanding life experiences, development, learning and inclusion. This research contributes to the areas of education and psychology, and is part of the research line Educational Processes, Language, Technology and Inclusion by the Postgraduate Program in Education (PPGEdu) of the University of Caxias do Sul (UCS). [resumo fornecido pelo autor]
Esta dissertação tem como foco o estudo do desenvolvimento e aprendizagem da criança com deficiência intelectual. A perspectiva teórica escolhida é a teoria histórico-cultural e o modelo social da deficiência. Entende-se, ainda, que o brincar é essencial para o desenvolvimento infantil, pois promove desenvolvimento e aprendizagem através da ampliação das funções psíquicas superiores, fortalecimento de vínculos afetivos e acesso aos bens culturais. Nessa direção, articulações entre a deficiência e o brincar são tecidas. Assim, o objetivo geral da pesquisa é investigar o brincar de crianças com deficiência intelectual em idade pré-escolar (de 3 a 6 anos), à luz da teoria histórico-cultural. Como objetivos específicos, tem-se: a) caracterizar a deficiência intelectual a partir dos pressupostos da teoria histórico-cultural de Vigotski e da perspectiva do modelo social da deficiência; b) explicitar conceitos da teoria histórico-cultural de Vigotski, centrais para compreender o desenvolvimento e aprendizagem da criança com deficiência intelectual; c) descrever o brincar na educação infantil, com foco nas contribuições da teoria histórico-cultural clássica e contemporânea; d) situar, a partir da teoria histórico-cultural, quais os eixos para pensar o brincar da criança com deficiência intelectual em idade pré-escolar, a fim de sinalizar possíveis intervenções para o campo da educação e da psicologia. Trata-se de uma pesquisa qualitativa, exploratória, cujo percurso metodológico consiste em uma pesquisa teórico-conceitual. Elegeu-se o modo de conhecimento analítico como produção de conhecimento científico. Os resultados da investigação demonstram que brincar de faz de conta é a atividade-guia de crianças em idade pré-escolar, sendo fundamental para o desenvolvimento da imaginação e criatividade, emancipação da realidade, reconhecimento dos papéis sociais, zona de desenvolvimento proximal e funções psíquicas superiores também para as crianças com deficiência intelectual. Além do mais, o brincar coletivo de crianças com deficiência intelectual com seus pares (com ou sem deficiência) e adultos favorece a interação social, ludicidade, imaginação, imitação, evolução das funções psicológicas superiores, especialmente o pensamento, fala, memória e atenção, e a criação da zona de desenvolvimento proximal, graças à mediação do professor. Conclui-se que, para crianças com deficiência intelectual em idade pré-escolar, tanto o brincar de faz de conta como o brincar coletivo são formas de acesso aos bens culturais e sociais e, portanto, de ampliação das experiências de vida, desenvolvimento, aprendizagens e inclusão. A presente pesquisa contribui para as áreas da educação e psicologia, situando-se na linha de pesquisa Processos Educacionais, Linguagem, Tecnologia e Inclusão pelo Programa de Pósgraduação em Educação (PPGEdu) da Universidade de Caxias do Sul (UCS). [resumo fornecido pelo autor]
Keywords: Incapacidade intelectual - Educação; Crianças - Recreação; Crianças - Desenvolvimento; Educação pré-escolar; Aprendizagem; Psicologia educacional; Vigotsky, Lev Semenovich, 1896-1934; Stupidity - Education; Children - Recreation; Children - Development; Education, Preschool; Learning; Educational psychology